2015
DOI: 10.1002/anie.201411957
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Dehydropolymerization: A Convenient Route to Poly(phosphinoboranes) with Molecular‐Weight Control

Abstract: The catalyst loading is the key to control the molecular weight of the polymer in the iron-catalyzed dehydropolymerization of phosphine-borane adducts. Studies showed that the reaction proceeds through a chain-growth coordination-insertion mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 67 publications
11
83
1
1
Order By: Relevance
“…The M06-2X functional2021 was used for the gas-phase geometry optimization of all species, which was demonstrated to be suitable for studying transition metal catalysis2223. The LANL2DZ basis set24 was employed for Rh and Fe, and the 6–31 G(d) basis set was used for other atoms (GEN1).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The M06-2X functional2021 was used for the gas-phase geometry optimization of all species, which was demonstrated to be suitable for studying transition metal catalysis2223. The LANL2DZ basis set24 was employed for Rh and Fe, and the 6–31 G(d) basis set was used for other atoms (GEN1).…”
Section: Computational Detailsmentioning
confidence: 99%
“…We have shown that the reactions of the monomeric phosphanylboranes 1a and 1b with the main group Lewis acids BH 3 and BBr 3 lead to the compounds 2a-3b. The secondary and tertiary phosphines 1a and 1b behave as classical Lewis bases and coordinate to BX 3 (X = H, Br) as terminal groups.…”
Section: Discussionmentioning
confidence: 99%
“…E.g., it was shown that the poly(phosphinoborane) [RHP-BH 2 ] n (R = p-CF 3 C 6 H 4 ) can be used as an electron beam resist for lithographic applications. [1,4] The parent poly(phosphinoborane) [H 2 P-BH 2 ] n was prepared for the first time via B(C 6 F 5 ) 3 -catalyzed dehydrocoupling of H 3 P·BH 3 . A mixture of oligomers and low molar mass polymers (M n Ͻ 2000 g·mol -1 ) was obtained, which showed high sensitivity and decomposed under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[9][10][11] In particular, amine-borane adducts have attracted considerable interest as potential hydrogen storage molecules. 15,16 In 1999 the Manners' group pioneered the use of transition metal catalysts in the synthesis of poly(phosphinoboranes) [17][18][19][20] and more recently B(C 6 F 5 ) 3 has been used as a metal-free dehydrocoupling catalyst. 11,14 Dehydrocoupling of phosphine-boranes to form poly(phosphinoboranes) was first reported in the 1950s.…”
Section: Introductionmentioning
confidence: 99%